1988
DOI: 10.1111/j.1600-065x.1988.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforin‐Dependent and ‐Independent Pathways of Cytotoxicity Mediated by Lymphocytes

Abstract: There is little doubt at the present time that both perforin-dependent and -independent pathways are important in mediating the cytotoxicity associated with lymphocytes. The cell distribution of perforin, initially thought to include both CTL and NK cells, now must be viewed with caution because all previous biochemical studies on CTL have been conducted with cell lines propagated in long-term cultures in the presence of T cell growth factors (IL-2 and perhaps some still undefined factors). Under these conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 221 publications
0
23
1
Order By: Relevance
“…Although inhibition of endothelial cell growth and survival may serve as a brake on the inflammatory response during the early stages of endothelial activation, this growth inhibition may contribute to pathophysiologic responses in the later stages of cytokine-mediated diseases. For example, in septic shock, neutrophil-and lymphocyte-mediated endothelial cell injury and loss of monolayer integrity may go unrepaired, which in turn would accelerate vascular leakage and increase leukocyte adhesion to the endothelial surface long after the initial infectious insult had subsided (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibition of endothelial cell growth and survival may serve as a brake on the inflammatory response during the early stages of endothelial activation, this growth inhibition may contribute to pathophysiologic responses in the later stages of cytokine-mediated diseases. For example, in septic shock, neutrophil-and lymphocyte-mediated endothelial cell injury and loss of monolayer integrity may go unrepaired, which in turn would accelerate vascular leakage and increase leukocyte adhesion to the endothelial surface long after the initial infectious insult had subsided (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…So far, two models for lymphocytemediated cytotoxicity have been proposed-the granule exocytosis model and the induced suicide model (1)(2)(3)(4). Recently, the effector molecules in the former, such as perforin (4) and granzymes (5), have been identified and it has been confirmed that the perforin-dependent mechanism constitutes one primary pathway of CTL-mediated cytotoxicity by the transfection (6) and gene targeting (Hidefumi Kojima and N.S., unpublished data; ref.…”
mentioning
confidence: 99%
“…That the average Pfp content per cell is reduced among effector cell populations exhibiting reduced lytic activity suggests that a critical intracellular level of Pfp may be required to produce potent and efficient lytic effector cells. Thus, cells with reduced Pfp levels, such as MLC-stimulated cells from aged mice, may be less efficient for enabling Pfp polymerization [8] and inducing lysis of target cells, andor for recycling to kill additional target cells.…”
Section: Discussionmentioning
confidence: 97%